Self-management approaches for diabetic patients in the context of digital healthcare: a concept analysis - Kumari, Ritu; Prathiba, P. M.; Meena; Kalyani, B.; Khichi, Manmohan Singh; Saini, Pooja; Suhashini; Monteiro, Rita Juliet; Mohammed Umar (International Journal Of Community Medicine And Public Health, 2025)
Effective self-management is central to diabetes care, improving glycaemic control and patient outcome. The rapid growth of digital health-defined as the use of information and communication technologies (mobile apps, wearables, telemedicine, etc.) to manage illness and promote wellness offers new tools for diabetes self-care. To clarify the concept of self-management approaches for diabetic patients in the context of digital healthcare using Walker and Avant’s eight-step method of concept analysis. Authors conducted a structured concept analysis. A comprehensive search of the literature (PubMed, CINAHL, MEDLINE and Google Scholar) was performed for terms related to “diabetes self-management”, “digital health” and “eHealth interventions”. Seminal works and definitions were consulted. Walker and Avant’s framework guided the analysis steps used. The concept is defined as the use of digital technologies by patients with diabetes to actively monitor, make decisions about and carry out health-related behaviors in managing their condition. Defining attributes were identified. Patient engagement and empowerment–active participation in care and confidence in self-care decisions. Data-informed decision-making–systematic self-monitoring (e.g., glucose, activity) with actionable feedback. Use of technology–integration of digital tools (apps, wearable sensors, telemedicine) to support self-care. Personalized and goal-directed actions–individualized goal setting (diet, exercise, medication adherence) and tailored education. Connectivity and support–ongoing communication with healthcare providers or peer networks via digital platforms. Self-management in the digital era for diabetes encompasses active, tech-enabled patient behaviors guided by data and support.